An Experimental Study on the Wind-Induced Response of Variable Message Signs - Meyer, Debbie; Zisis, Ioannis; Hajra, Bodhisatta; Gan Chowdhury, Arindam; Irwin, Peter (Frontiers in Built Environment, 2017)
Variable Message Sign (VMS) systems are widely used in motorways to provide traffic information to motorists. Such systems are subjected to wind-induced structural vibration that can lead to damage due to fatigue. The limited information that is available on the safe wind design of VMS motivated a large scale testing that was conducted at the Wall of Wind (WOW) Experimental Facility at Florida International University (FIU). One of the objectives of the present study was to experimentally assess the wind-induced force coefficients on VMS of different geometries and utilize these results to provide improved design guidelines. A comprehensive range of VMS geometries were tested and mean normal and lateral force coefficients, in addition to the twisting moment coefficient and eccentricity ratio, were determined using the measured data for each model, for wind directions of 0o and 45o. The results confirmed that the mean drag coefficient on a prismatic VMS is smaller than the value of 1.7 suggested by American Association of State Highway and Transportation Officials (AASHTO). An alternative to this value is presented in the form of a design matrix with coefficients ranging from 0.98 to 1.28, depending on the aspect and depth ratio of the VMS. Furthermore, results indicated that the corner modification on a VMS with chamfered edges demonstrated a reduction in the drag coefficient compared to sharper edges. Finally, the dynamic loading effects were considered by evaluating the gust effect factor, using the ASCE 7 formulations, for various VMS weights and geometries. The findings revealed a wide range of possible gust effect factors, both above and below the current AASHTO specification of 1.14. Future research may include different geometries of VMS and a wider range of wind directions.